Design Strategies of Biodegradable Scaffolds for Tissue Regeneration. (January 2014) - Bitar, Khalil N.; Zakhem, Elie
There are numerous available biodegradable materials that can be used as scaffolds in regenerative medicine. Currently, there is a huge emphasis on the designing phase of the scaffolds. Materials can be designed to have different properties in order to match the specific application. Modifying scaffolds enhances their bioactivity and improves the regeneration capacity. Modifications of the scaffolds can be later characterized using several tissue engineering tools. In addition to the material, cell source is an important component of the regeneration process. Modified materials must be able to support survival and growth of different cell types. Together, cells and modified biomaterials contribute to the remodeling of the engineered tissue, which affects its performance. This review focuses on the recent advancements in the designs of the scaffolds including the physical and chemical modifications. The last part of this review also discusses designing processes that involve viability of cells.